Biocompatibility and features of degradation of polymer anti-adjection membranes with antibacterial activity - Yu. A. Kudryavtseva; A. Yu. Kanonykina; N. A. Efremova; V. A. Koshelev (Фундаментальная и клиническая медицина)
When performing operations on the abdominal and thoracic organs, the main share of postoperative complications is represented by the formation of adhesions or the development of an infectious process, which leads to a decrease in the quality of life of patients, the need for reoperation and often causes deaths. A solution to this problem can be the use of intraoperative biodegradable anti-adhesion membranes that have their own antibacterial activity.Aim. Development of polymer anti-adhesion membranes with their own anti-inflammatory and antibacterial activity, assessment of their biocompatibility and biodegradation in in vivo experimentsMaterials and Methods. The membranes are made by electrospinning from a composition of biodegradable polymers: polylactide-co-glycolide copolymer (50:50) and polylactide-co-glycolide (85:15). To impart antibacterial properties to the membrane, the antibiotic Tigacil was added to the polymer solution in various dosages - 0.125; 0.25 and 0.5 mg/ml polymer solution. The antibacterial activity of the membranes in vivo was assessed. The physical and mechanical properties were studied and the surface structure of the membranes was assessed using a scanning electron microscope. Biocompatibility and dynamics of biodegradation were assessed in vivo by implantation into laboratory animals (rats) for periods of 14 days, 1, 2 and 3 months, followed by histological examination of explanted samples.Results. Polymer membranes made by electrospinning, without the inclusion of Tigacil, consist of threads whose thickness was 1.63 microns (1.422.85 microns); when Tigacil is included in the fiber composition, the fiber thickness decreases to 1.2 microns (0.977 - 1.89 pm), while the threads are more densely and orderly located. The strength and elasticity modulus of membranes with Tigacil are almost 2 times higher than those of samples without the inclusion of the drug. The maximum antibacterial effect was achieved at a Tigacil dosage of 0.5 mg/ml - the zone of inhibition of Staphylococcus aureus at a Tigacil concentration of 0.125 mg/ ml was 146%, 0.25 mg/ml - 152% and at a concentration of 0.5 mg/ml - 11 .5 mm 177%. The inclusion of Tigacil led to a decrease in the rate of biodegradation of samples in vivo. The samples underwent biodegradation without signs of acute and chronic inflammation.Conclusion. The inclusion of Tigacil in the membrane gives it antibacterial properties, and the optimal concentration of Tigacil was 0.5 mg/ml of the polymer solution. The inclusion of Tigacil in the polymer composition affects the morphology of the membranes, increases the strength and elastic modulus, which led to a decrease in the rate of degradation when implanted subcutaneously in rats. The absence of signs of inflammation confirms the biocompatibility of the developed membranes.